Organization of practice as a key factor in the formation of cognitive activity of students of pedagogical specialties (Pedagogy of Higher and Secondary Education, 2013)
Ternavskaya T. A. Organization of practice as a key factor in the formation of cognitive activity of students of pedagogical specialties.The article is dedicated to the process of organization and conducting practices. It is defined the peculiarities of forming cognitive activity to pedagogy students while preparing them to practice.
Keywords: cognitive activity; preparing to practice